2021
DOI: 10.1007/s13300-021-01125-8
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tofogliflozin on Treatment-Related Quality of Life in Patients with Type 2 Diabetes Mellitus

Abstract: Introduction Treatment-related quality of life (QOL) is an important aspect of diabetes management. We evaluated the influence of a sodium-glucose cotransporter 2 (SGLT2) inhibitor, tofogliflozin, on treatment-related QOL in Japanese patients with type 2 diabetes mellitus (T2DM). Methods This is the prespecified subanalysis study of the “Using TOfogliflozin for Possible better Intervention against Atherosclerosis for type 2 diabetes patients (UTOPIA)” trial. Treatment-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Additionally, the UTOPIA study of clinical cases revealed that TOFO exhibits exceptional therapeutic effects on atherosclerosis. 42 , 43 Therefore, the combination therapy with TOFO may represent an optimal treatment strategy for diabetes, encompassing measures against atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the UTOPIA study of clinical cases revealed that TOFO exhibits exceptional therapeutic effects on atherosclerosis. 42 , 43 Therefore, the combination therapy with TOFO may represent an optimal treatment strategy for diabetes, encompassing measures against atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…PWV response can often occur independent of systolic BP levels. 4,5 Therefore, a lingering question persists: Could arterial stiffness be a more significant risk factor for CSVD progression and a more appropriate treatment target than hypertension in stroke-free individuals?…”
Section: See Related Article P 2814mentioning
confidence: 99%
“…In addition to its effect on glycemic control, tofogliflozin improves high-density lipoprotein cholesterol (HDL-C) and triglyceride (TG) levels, decreases body weight and blood pressure, and elevates circulating adiponectin levels [ 11 ]. We previously investigated the effect of tofogliflozin on carotid artery intima-media thickness (IMT) [ 12 ], which is a marker of atherosclerosis [ 13 ], arterial stiffness [ 14 ], and patients’ quality of life (QOL) [ 15 ], in the “Using TOfogliflozin for Possible better Intervention against Atherosclerosis for type 2 diabetes patients (UTOPIA)” trial. Although tofogliflozin did not delay the progression of IMT thickening, it significantly improved glycemic control, body weight, body mass index (BMI), abdominal circumference, systolic blood pressure, HDL-C, arterial stiffness, and treatment-related QOL [ 12 , 14 , 15 ] during the 2-year intervention period.…”
Section: Introductionmentioning
confidence: 99%